(untitled) (International journal of artificial intelligence, 2025)
This article examines the importance of working on vocabulary in Russian language and literature lessons as one of the key aspects of students' speech development. The author analyzes the stages of vocabulary work, including semanticization, activation, and the application of words in speech, and proposes effective methodological approaches and exercises for expanding students' vocabulary. The article emphasizes the necessity of a systematic and purposeful study of vocabulary, integrated into all sections of the Russian language curriculum. Drawing on the works of leading linguists and methodologists, the author argues that activating students' vocabulary not only improves their speech skills but also contributes to the formation of moral values. This work may be useful for Russian language teachers, methodologists, and researchers in the fields of pedagogy and linguistics.